R Storeworld2019 / Muhammad Akmal Mustafa - Mustafa, Muhammad Akmal (2021)
R storeworld2019 is online retailer of trendy marked and streetwear. The fundamental objective of R storeworld2019 is to give the most ideal popular things from different brand to the customer. Consumer loyalty and add to grow design and streetwear local area. R storeworld2019 has been in the business since December 2019. Beginning of R storeworld2019, the business just sell utilized streetwear like shirt and covers through Instagram. Through most of the way of the year 2020, the busines change its idea from sell just utilized streetwear to bring some fresh out of the box new streetwear into the business. Presently, the business center more around selling brand new items because of more appeal. R storeworld2019 additionally has its own image which is Rstoreworld and as yet wanting to deliver its own item later on. Web-based media is an incredible medium to extend the business and Facebook is the principle decision since it has the most web-based media clients contrast with other web-based media. The higher the users the higher the expected customers. The business situated in Klang, Selangor and furthermore offer cash on delivery services restricted distinctly in Klang Valley region. Different regions can make installment through online transfers and we will post the items using J&T and Pos Laju delivery services. R storeworld2019 only sell bona fide items and against the selling of fake items. We give security to our customers where we will follow through on back multiple times from selling cost if our items discovered fake. Trust is the main reasons in business and we attempting to acquire it. R storeworld2019 target market is people between the age of 17-40 who love to dress up well. This is on the grounds that we sell aunthentic elegant and relaxed wear. Consequently, individuals who have their own pay and still dynamic to spend time with their companions is our main target. To wrap things up, R storeworld2019 will utilize all sort of online medium to showcase the business as long as its legitimate. This to build the consciousness of online clients that R storeworld2019 is exist. Social media like Facebook and the use of teaser, hard-selling and soft-selling will help the business with growing locally as well as globally.